The employment of women in Great Britain 1891-1921 - Hogg, S (1967)
This is a study of women’s employment in Great Britain from 1891 to 1921 with special reference to its division from men’s. It examines, first, the occupational distribution of the nation’s labour force during the 1891-1914 period and finds a definite division between the work done by women and the work done by men. It then asks what factors underlay women’s absence from the work men did and women’s presence and men’s absence from the work women did. After answering these questions it shows and accounts for the major changes that occurred in women’s employment between the pre-First World War years of 1891 to 1914, the First World War years of 1914 to 1918, and the post-First World War years of 1918 to 1921 and considers what effect they had on the sex division of labour. Of secondary interest is the reaction of women to their own employment position. The 1891-1921 period coincides with the advance of the so-called women’s rights movement whereby women, as active agents in furthering their interests as citizens, wives, mothers, and persons, also undertook to improve their position as workers. Why was there dissatisfaction with it? What were the measures taken to better it? How effective were they? What did they signify for the division of labour? This thesis encompasses these questions as well. Descriptively this thesis sets out, in more statistical and narrative detail than has ever before been attempted for the 1891-1921 period and for Great Britain as a whole, the existence of a sex division of labour, secondly, its extensiveness, and thirdly, the position of the dividing line. Analytically it isolates the principal factors affecting the determination of what was women’s and what was men’s work. In the process it shows that any analysis that begins with the character of the supply and demand for male and for female labour as given facts cannot adequately explain the sex division as it fails to explain why sex as such appears as a differentiating factor. For this, account must be taken of how males and females were transformed into masculine and feminine persons and how masculinity and femininity as contemporaneously defined affected a person's labour attributes and, directly and indirectly, an employer’s choice of labour. Finally, this thesis, by considering women’s employment over a period of time, becomes a record of how it changed as the factors affecting its determination were modified. Moreover, by focusing attention on the contemporary developments making for change between 1891 and 1921, this thesis provides a springboard for analyzing subsequent changes in women’s employment.